STRATEGIES IN TRANSLATING METONYMIES: A CASE STUDY IN THE TRANSLATIONS OF THE NOVELS EXCLUSIVE BY SANDRA BROWN AND A POCKET FULL OF RYE BY AGATHA CHRISTIE INTO INDONESIAN) - Gitawati, Novi Dwi; Said, Mashadi (Universitas Gunadarma, 2014)
As one of figures of speech, people often use metonymy when they want to refer to one entity by means of another entity based on their contiguity. In translation, this figure of speech can sometime pose a problem, as the target language readers may not culturally accustom with the metonymy that the source language text uses to make reference to a particular entity. By relying on Chesterman’s trope change strategy (or rather a set of strategies), this research attempted to analyze the strategies used in translating _nglish_es found in the novels Exclusive by Sandra Brown and A Pocket Full of Rye by Agatha Christie, which are used as the source of the data in this research. The method used in this research is the descriptive-analytical method. Based on the analysis, the researcher found that the metonymies are translated into two out of three subclasses of the trope change strategy, namely: translating the figurative expression in the same form as the SL figurative expression (ST trope X → TT trope X) and translating the figurative expression plainly into a non-figurative expression in TLT (ST trope X → TT trope Ø). Key words: metonymy, Chesterman’s trope change strategy